2014
DOI: 10.1111/nin.12068
|View full text |Cite
|
Sign up to set email alerts
|

The ethical tightrope: politics of intimacy and consensual method in sexuality research

Abstract: This paper seeks to analyze the construction of ethics in sexuality research in which qualitative methods are employed in the field of social sciences. Analyses are based on a bibliographic review of current discussions on research methods of queer theory and on the authors' own experiences of past research on sexuality. The article offers a theoretical perspective on the ways ethnography and in-depth interviews become methods that can rely on a consensual method and create a politics of intimacy between the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Due to the deeply personal and sensitive nature of sex research, concerns have been raised about using human participants in researching sex and about protecting research participants when talking about sensitive and personal aspects of sexuality (Zago & Holmes, 2015;Zuch, Mason-Jones, Mathews, & Henley, 2012). A focus on publicly available online narratives of stealthing circumvents some of these concerns, yet provides accessibility to naturalistic information.…”
mentioning
confidence: 99%
“…Due to the deeply personal and sensitive nature of sex research, concerns have been raised about using human participants in researching sex and about protecting research participants when talking about sensitive and personal aspects of sexuality (Zago & Holmes, 2015;Zuch, Mason-Jones, Mathews, & Henley, 2012). A focus on publicly available online narratives of stealthing circumvents some of these concerns, yet provides accessibility to naturalistic information.…”
mentioning
confidence: 99%
“…It has been suggested that in-depth interviews on sexuality create a politics of intimacy between research participant and researcher, a politics that may be a part of creating politically engaged knowledge (Plummer, 1995;Zago & Holmes, 2015). To us, adhering to the needs of the research participants has outweighed adhering to the traditional moral matrix, which can feel restricting in how an interview situation ideally "should" be.…”
Section: Discussionmentioning
confidence: 99%
“…La recolección puede implicar la presencia del investigador en momentos considerados personales, íntimos, privados o restringidos exclusivamente a miembros selectos del grupo, algunos de estos momentos pueden no haber sido previstos de antemano, sino que se presentan a lo largo del desarrollo investigativo (43). De otra parte, la observación etnográfica puede potencialmente llevar a situaciones extremas como cuando el investigador es testigo de conductas delictivas o se ve envuelto en situaciones en las que se desarrollen relaciones entre el investigado y el investigador, que van más allá de la confianza que debe generarse para el éxito del proceso (44).…”
Section: Establecer El Riesgounclassified